Solvable product-type system of difference equations with two dependent variables - Stevo Stević (Advances in Difference Equations, 2017)
Abstract It has been recently noticed that there is a finite number of two-dimensional classes of product-type systems of difference equations solvable in closed form. We present a new class of this type. A detailed analysis of the form of its solutions is given. Our results complement the previous ones on such systems and present one of the final steps in describing the forms of their solutions.